1991
DOI: 10.1128/jcm.29.12.2835-2837.1991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liquid media for growth of Helicobacter pylori

Abstract: Helicobacter pylori has routinely been isolated and grown on solid media. Recently, we have succeeded in obtaining growth of this organism in several liquid media in large volumes, including tryptic soy broth, Mueller-Hinton broth, brucella broth, brain heart infusion broth, and Columbia broth. Growth was tested in the media with and without supplementation. Growth was obtained after incubation under microaerobic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…Brucella broth is a complex medium composed of tryptone 10 g [-1, peptamin 10 g 1-1, dextrose 1 g 1-1, yeast extract 2 g 1-1, sodium chloride 5 g 1-1 and sodium bisulfite 0.1 g 1-1. This medium was described in many articles as capable of supporting the growth of H. priori only when supplemented with blood derivatives [8][9][10]. A substantial simplification of H. pylori growth media was obtained recently when it was discovered that cyclodextrins could be used in the place of blood derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucella broth is a complex medium composed of tryptone 10 g [-1, peptamin 10 g 1-1, dextrose 1 g 1-1, yeast extract 2 g 1-1, sodium chloride 5 g 1-1 and sodium bisulfite 0.1 g 1-1. This medium was described in many articles as capable of supporting the growth of H. priori only when supplemented with blood derivatives [8][9][10]. A substantial simplification of H. pylori growth media was obtained recently when it was discovered that cyclodextrins could be used in the place of blood derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…This cannot be achieved with current technology for H. pylori growth. Laboratory growth of H. pylori is difficult and normally requires complex media containing sera, blood or blood derivatives [8][9][10] that interfere with the purification procedures of the proteins to be tested. It was recently shown that the addition of cyclodextrins (CDs) to the media can substitute for the above-mentioned additives to sustain the growth of this fastidious organism [11].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial mechanisms of the drugs may be more effective under these conditions because the microorganisms are metabolically more active or because contact events with drug molecules occur more frequently due to the motility of the organisms. In this respect, it is of interest that both Morgan et al [29] and Shahamat et al [30] reported that H. pylori cells grown in fluid media containing Brucella broth and serum supplements were uniformly spiral‐shaped (and thus, regarded to be fully viable), while a varying proportion of cells grown on solid media had a coccoid appearance which is thought to indicate a dormant, metabolically down‐regulated state of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…One medium that the author has found satisfactory for maintenance culture is Columbia agar base + 5% horse blood + 1% isovitalex. In some circumstances, large but not industrial‐scale volumes of bacterial growth are required, in which case H. pylori can be grown readily in any of the complex liquid media [54,55] or defined media already mentioned, provided the culture is aerated adequately.…”
Section: Culture Of H Pylori For Research Purposesmentioning
confidence: 99%